Moonlight, Dickinson County - Caldwell, Dakota (Kansas State University, The Chapman Center for Rural Studies, 2016)
Moonlight, located in Hayes Township, Dickinson County, Kansas, was founded by members of the Brethren in Christ Church migrating from Pennsylvania. It thrived temporarily, for about forty years, but dried up as business moved to larger towns and citizens moved away.
Dakota Caldwell, “Moonlight, Dickinson County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/206.
Keywords: Brethren in Christ Church; Dickinson; Dickinson County; Kansas Pacific; Moonlight; Thomas Moonlight